Qualitative Modeling to Analyze The Performance of Beef Cattle Farms That Receive Government Aid in Banyumas District - Kusumasari, Tria Permata; Setianto, Novie Andri; Wakhidati, Yusmi Nur; Muatip, Krismiwati; Setyaningrum, Agustinah (Buletin Peternakan, 2025)
The objectives of this study are to analyze the success of the beef cattle assistance program in Banyumas Regency as seen from the economic performance of the business and to identify the factors related to the performance of beef cattle farms receiving assistance in Banyumas. This study used a field survey method in Purwojati and Jatilawang Subdistricts, Banyumas Regency with in-depth discussions and interviews (focus group discussions). The sample size was determined using purposive sampling. There were 65 informants from 4 groups of beef cattle farmers who received assistance in 2021 and 2022. Data analysis using Cash Flow and Causal Loop Diagram (CLD) qualitative modeling. The results of the cash flow analysis research found that one farmer group was considered efficient, one was inefficient, and the other two groups could not be identified because there was no revenue and expenditure data. Factors related to business performance of beef cattle farmers in Banyumas Regency based on Causal Loop Diagram were found to be livestock suitability, violation, motivation, and feed.